THE ROLE OF BANKS IN GREEN ECONOMY AND SUSTAINABLE DEVELOPMENT - Nuriddinova Sitorabonu Utkir qizi (Modern American Journals, 2025)
This article analyzes the role of the banking system in the processes of developing a green economy and achieving sustainable development. In the modern era, ensuring environmental safety, rational use of natural resources, and minimizing negative impacts on the environment have become key directions of global economic policy. In this context, banks and financial institutions are increasingly incorporating the principles of “green finance” into their activities to support environmentally friendly, energy-efficient, and sustainable projects. Using the example of Uzbekistan’s banking system, the article examines the practice of green lending, mechanisms for financing ecological innovations, and the role of the banking sector in the implementation of sustainable development strategies. The results of the study show that the development of a green finance system plays a crucial role in strengthening the ecological balance of the national economy, creating new employment opportunities, and achieving long-term economic stability.
Keywords: Green economy, sustainable development, green finance, banking system, ecological investment, green lending, energy efficiency.